2017
DOI: 10.1080/10942912.2017.1315131
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization and antioxidant activities of the edible part of globe artichoke cultivars grown in Tunisia

Abstract: A renewed interest was observed recently in the globe artichoke as a promising source of polyphenols, a heterogeneous class of secondary metabolites characterized by various well-documented healthy properties. However, only few studies characterized Tunisian cultivars. Therefore, the present study aimed at evaluating the chemical parameters [fatty acids (FA), volatiles and phenolic derivatives content] in the edible part, the receptacle, of two globe artichoke cultivars (‘Violet d’Hyéres’ and ‘Blanc d’Oran’), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 33 publications
0
8
0
3
Order By: Relevance
“…The UHPLC-QTOF analysis also revealed traces of anthocyanins in artichoke leaf extracts, with the highest value in the ‘Istar’ cultivar ( Table 2 ). Previous works also reported that flavones and phenolic acids are the main compounds of artichoke leaf extracts [ 19 , 25 , 26 , 27 , 28 , 29 ]. Anthocyanins are the main flavonoid class responsible for blue/purple color in many plant tissues and, in particular, for the pigmentation of the globe artichoke bracts.…”
Section: Resultsmentioning
confidence: 98%
“…The UHPLC-QTOF analysis also revealed traces of anthocyanins in artichoke leaf extracts, with the highest value in the ‘Istar’ cultivar ( Table 2 ). Previous works also reported that flavones and phenolic acids are the main compounds of artichoke leaf extracts [ 19 , 25 , 26 , 27 , 28 , 29 ]. Anthocyanins are the main flavonoid class responsible for blue/purple color in many plant tissues and, in particular, for the pigmentation of the globe artichoke bracts.…”
Section: Resultsmentioning
confidence: 98%
“…Dabbou et al. (2017) identified sesquiterpenes hydrocarbons as the main chemical class of C . scolymus in particular β‐selinene, followed by β‐caryophyllene.…”
Section: Discussionmentioning
confidence: 99%
“…No bioloģiski aktīvajiem savienojumiem, augstākā antiradikālā aktivitāte raksturīga polifenoliem un C vitamīnam. Antiradikālā aktivitāte atšķiras no pielietotās kolorimetriskās metodes (Dabbou et al, 2017;Mabeau et al, 2007). Polijā konstatēts, ka atkarībā no metodes, analizējot ekstraktu, kas iegūts no lodveida artišoku lapām šķirnei 'Green Globe', antiradikālā aktivitāte bija no 44% (DDPH metode) līdz 80% (ABTS metode) (Biel et al, 2019).…”
Section: Agroekoloģisko Faktoru Ietekme Uz Artišoku Galviņu Bioķīmisko Sastāvuunclassified
“…Polijā konstatēts, ka atkarībā no metodes, analizējot ekstraktu, kas iegūts no lodveida artišoku lapām šķirnei 'Green Globe', antiradikālā aktivitāte bija no 44% (DDPH metode) līdz 80% (ABTS metode) (Biel et al, 2019). Savukārt Tunisijā audzējot divas šķirnes un analizējot pēc DPPH metodes, antiradikālā aktivitāte bija noteikta 63 un 70% (Dabbou et al, 2017). Ierīkotajā izmēģinājumā abu gadu periodā antiradikālā aktivitāte (nosakot pēc DDPH metodes) vidēji variēja no 41 līdz 68% (3.45.…”
Section: Agroekoloģisko Faktoru Ietekme Uz Artišoku Galviņu Bioķīmisko Sastāvuunclassified
See 1 more Smart Citation